Open spaces: The new frontier for academic writers - Moodley, P. (South African Journal of Higher Education, 2017)
In the face of the ‘fees must fall’ campaign and severe budgetary constraints for South African universities, funding has become a challenge. To this end, institutional management bodies look to academics to fill the gaping void of reduced budgets through increased research output. This has sparked the need for institutions to provide support in the form of writing retreats for academics. The current study offers a critical examination of the experiences of academics on writing retreats, as well as the barriers they encountered once the retreat was over. Data was collected via qualitative in-depth interviews (n=3). Content analysis was carried out on the data which revealed barriers to publication such as the need for additional support and time constraints. On this basis, this study recommends a model for Publication Improvement which is proposed to address the barriers academics encountered.